Guideline Adherence of Paediatric Urolithiasis: An EAU Members' Survey and Expert Panel Roundtable Discussion - Beatriz Bañuelos Marco; Bernhard Haid; Anna Radford; Thomas Knoll; Sajid Sultan; Anne-Françoise Spinoit; Manuela Hiess; Simone Sforza; Rianne J. M. Lammers; Lisette Aimée 't Hoen; Edoardo Bindi; Fardod O'Kelly; et al. (MDPI AG, 2022)
Background: Paediatric nephrolithiasis has increased globally, requiring standardized recommendations. This study aims to assess the paediatric urolithiasis care between EAU members along with the statements of three experts in this field. Methods: The results of an electronic survey among EAU members comparing the guideline recommendations to their current practice managing paediatric nephrolithiasis in 74 centres are contrasted with insights from an expert-panel. The survey consisted of 20 questions in four main sections: demographics, instrument availability, surgical preferences and follow-up preferences. Experts were asked to give insights on the same topics. Results: A total of 74 responses were received. Computerised Tomography was predominantly used as the main imaging modality over ultrasound. Lack of gonadal protection during operations was identified as an issue. Adult instruments were used frequently instead of paediatric instruments. Stone and metabolic analysis were performed by 83% and 63% of the respondents respectively. Conclusions: Percutaneous Nephrolithotomy is the recommended standard treatment for stones > 20 mm, 12% of respondents were still performing shockwave lithotripsy despite PNL, mini and micro-PNL being available. Children have a high risk for recurrence yet stone and metabolic analysis was not performed in all patients. Expert recommendations may guide clinicians towards best practice.